59 Real world TAVI outcome and prognostication: a retrospective review of a single centre experience. (7th October 2015) - Howe, A; Spence, M; Manoharan, G; Johnston, N; Owens, C; Dixon, L; Onyekwelu, N; Jeganathan, R; Smith, B; McEvoy, M
Abstract : Introduction: Trans-catheter aortic valve implantation (TAVI) is now an established treatment option for patients with severe symptomatic aortic stenosis who are at high or inoperable risk for surgical aortic valve replacement. Most of the established data are from studies of patients meeting strict inclusion and exclusion criteria. We present the complete experience from our centre including 1, 3 and 5 year outcomes and identify adverse prognostic factors. Method: A retrospective analysis of consecutive TAVI procedures within our centre was performed from 2008 to 2014 utilising the National Institute of Cardiovascular Outcomes (NICOR) database. Patient and procedural data were obtained with corroboration of outcome using the Northern Ireland Electronic Care Record (NIECR) system. Statistical analysis was performed using SPSS version 21. Kaplan-Meier survival curves were drawn to assess survival at 30 days, 1, 3 and 5 years. For predictors of outcome Cox regression was performed with a univariate analysis to determine significance (p < 0.05) and subsequent multivariate modelling. Results: From February 2008 to December 2014, 414 TAVI procedures were performed. Outcome data was available for 408 patients. The Medtronic Corevalve prosthesis was predominantly implanted (63.2%) with the majority of procedures performed under local anaesthesia (91.0%) via the femoral approach (90.7%). Significant (moderate or greater) aortic regurgitation (AR) assessed by trans-thoracic echocardiography occurred in 4.4%, with 13.2% of patients requiring permanent pacemaker implantation. Survival was 96.1% at 30 days, 85.5% at 1 year, 72.7% at 3 years and 49.2% at 5 years with no significant difference according to year of implantation (Figure 1 ). Univariate predictors of 1 year mortality were Logistic Euroscore (LES) >24 (HR 2.1; 95% CI 1.1–3.8, p = 0.02), moderate or greater AR (HR 4.5; 95% CI 2.0–10.1, p < 0.001) and creatinine > 150 ummol/L (HR 4.0; 95% CI 2.3–6.9, p < 0.001). Multivariate analysis confirmed AR and creatinine as independent predictors of 1 year mortality. Univariate predictors of 3 year mortality were LES >24, creatinine >150, atrial fibrillation, left ventricular dysfunction and AR. Multivariate analysis confirmed creatinine as the only independent predictor of 3 year mortality (HR 2.9; 95% CI 1.7–5.0, p < 0.001. Conclusion: This all-comers TAVI experience demonstrates encouraging results that are consistent with published data. Baseline renal function was the most powerful predictor of 1 and 3 year mortality with paravalvular regurgitation proving the most significant procedural marker of adverse outcome.